Mesenchymal Stem Cells-Derived Exosomes Ameliorate Ischemia/Reperfusion Induced Acute Kidney Injury in a Porcine Model - Huang, Jianni; Cao, Hao; Cui, Binbin; Ma, Xiaoyan; Gao, Ling; Yu, Chao; Shen, Fengchen; Yang, Xinyu; Liu, Na; Qiu, Andong; Cai, Guangyan; Zhuang, Shougang (Frontiers in Cell and Developmental Biology, 2022)
Exosomes are membrane-enclosed vesicles secreted by cells that contain a variety of biologically active substances, including proteins, nucleic acids and lipids. In this study, we investigated the therapeutic effects of the exosomes and underlying mechanisms in a miniature pig model of ischemia/reperfusion-induced acute kidney injury (I/R-AKI). The exosomes were extracted from cultured human umbilical cord derived mesenchymal stem cells (hUC-MSCs) and infused into a miniature pig model of ischemia/reperfusion-AKI. Our results showed that 120 min of unilateral ischemia followed by reperfusion and contralateral nephrectomy resulted in renal dysfunction, severe kidney damage, apoptosis and necroptosis. Intravenous infusion of one dose of exosomes collected from about 4 x 108 hUC-MSCs significantly improved renal function and reduced apoptosis and necroptosis. Administration of hUC-MSC exosomes also reduced the expression of some pro-inflammatory cytokines/chemokines, decreased infiltration of macrophages to the injured kidneys and suppressed the phosphorylation of nuclear factor-κB and signal transducer and activator of transcription 3, two transcriptional factors related to inflammatory regulation. Moreover, hUC-MSC exosomes promoted proliferation of renal tubular cells, angiogenesis and upregulation of Klotho and BMP-7, two renoprotective molecules and vascular endothelial growth factor A and its receptor. Collectively, our results suggest that injection of hUC-MSC exosomes could ameliorate I/R-AKI and accelerate renal tubular cell repair and regeneration and that hUC-MSC exosomes may be used as a potential biological therapy for AKI patients.